2000
DOI: 10.1046/j.1523-536x.2000.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Team Midwifery Care in a Tertiary Level Obstetric Service: A Randomized Controlled Trial

Abstract: Continuity of midwifery care was associated with a reduction in medical procedures in labor and a shorter length of stay without compromising maternal and perinatal safety. Continuity of midwifery care is realistically achievable in a tertiary obstetric referral service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 10 publications
1
40
0
1
Order By: Relevance
“…8 The first randomised controlled trials of continuity of midwifery care date back to the late 1980s 9 and many have followed including a number of Australian trials. [10][11][12][13][14][15] Other research has demonstrated the benefits of one-to-one 16 and caseload models of care. 17 Caseload models have also been shown to be beneficial for midwives, reducing burnout and improving retention.…”
Section: The Evidence For Changementioning
confidence: 99%
See 1 more Smart Citation
“…8 The first randomised controlled trials of continuity of midwifery care date back to the late 1980s 9 and many have followed including a number of Australian trials. [10][11][12][13][14][15] Other research has demonstrated the benefits of one-to-one 16 and caseload models of care. 17 Caseload models have also been shown to be beneficial for midwives, reducing burnout and improving retention.…”
Section: The Evidence For Changementioning
confidence: 99%
“…The randomised controlled trials on team midwifery showed positive outcomes with teams of six to eight midwives. 9,[11][12][13][14] In many settings in Australia, teams are now made up of 20 or more midwives who work rotating shifts through the maternity unit. It is hard to see how any amount of continuity of carer is possible with teams this size.…”
Section: The Evidence For Changementioning
confidence: 99%
“…Supervised by physicians, nurses or midwives, nitrous oxide is widely used as a safe analgesic in many parts of the world including Canada, Australia, Finland, United Kingdom and New Zealand (43 to 49%) (STAKES, 2006;NSW Department of Health, 2005;Biró et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This example of the inverse care law finally drove me to establishing a continuity of care model for women attending the public maternity clinics at a tertiary hospital in Melbourne. 61 Hart 62 describes the inverse care law as a classic reference reflecting ''a global shift of British medical and allied professionalism towards alliance with the mass of the people the profession serves.'' (p. 18) Whilst Hart 62 coined the term in relation to the availability of medical care, it can be just as easily applied to the provision of midwifery care at all levels.…”
Section: The Inverse Care Lawmentioning
confidence: 99%